Cultural Mapping Of Singapore Cinemas - Leary, C. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Conference on Film and Cinema (6-7 October 2011) jointly organized by the Wee Kim Wee School of Communication and Information, Nanyang Technological University and the Asia Research Institute, National University of Singapore to be held at the ARI Seminar Room, Tower Block, Level 10, Bukit Timah Road.